2012
DOI: 10.3342/ceo.2012.5.s1.s93
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Outcomes: A Comparison between Irradiated and Non-irradiated Ears

Abstract: ObjectivesRadiotherapy for head and neck tumors is known to potentially induce sensorineural hearing loss, which is possibly due to damage to the cochlear and/or auditory pathways. Since the success of cochlear implantation depends on a functional auditory nerve, this paper aims to study the hearing outcomes of cochlear implantation in irradiated ears.MethodsA retrospective study of cochlear implant recipients from our institution who had previously received radiotherapy for head and neck cancers was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…91 The outcome following CI surgery in RT patients has been reported in only small retrospective series or case reports, including in total 25 patients. [92][93][94][95][96][97][98][99] All the case control series showed good performance in RT patients, which was similar to the control groups. 92,94,95 Pediatric patients treated for medulloblastoma were also found to benefit from CIs.…”
Section: Cochlear Implants and Radiotherapysupporting
confidence: 67%
See 1 more Smart Citation
“…91 The outcome following CI surgery in RT patients has been reported in only small retrospective series or case reports, including in total 25 patients. [92][93][94][95][96][97][98][99] All the case control series showed good performance in RT patients, which was similar to the control groups. 92,94,95 Pediatric patients treated for medulloblastoma were also found to benefit from CIs.…”
Section: Cochlear Implants and Radiotherapysupporting
confidence: 67%
“…[92][93][94][95][96][97][98][99] All the case control series showed good performance in RT patients, which was similar to the control groups. 92,94,95 Pediatric patients treated for medulloblastoma were also found to benefit from CIs. 93 Some authors have suggested preoperative brain imaging to evaluate for the presence of central nervous system pathologies, such as demyelination, which could predict poorer outcome.…”
Section: Cochlear Implants and Radiotherapysupporting
confidence: 67%
“…As determined in nasopharyngeal cancer survivals, the retro-cochlear auditory pathways are not seriously damaged and remain functionally intact even in the longer term after RT [193]. Overall hearing outcomes after cochlear implantation for post- irradiated patients were found not to be worse than in patients who have had no prior RT to ear structures [194] and related complications are rare, though so far, no study has compared the incidence of complications of post-cochlear implantation in irradiated versus non-irradiated temporal bones [195,196]. Moreover, cochlear implant surgery and cochlear implant activity have not been seen to have harmful effects on vestibular function and balance [197].…”
Section: Hearing Lossmentioning
confidence: 99%
“…Postoperatively, surgeons must be prepared to deal with the sequalae of radiation effects on soft tissue including increased tension on wound closure, poorer healing, and potential for increased infection. These arguments further support the role of primary CI placement . Of course, there are potential drawbacks to CI at the time of primary oncologic surgery, which must be considered.…”
Section: Discussionmentioning
confidence: 99%